Deepfakes applications. Manipulation of audiovisual content and risks for users based on privacy policies - Boté Vericad, Juan José; Vállez, Mari (Documentación de las Ciencias de la Información, 2022)
The growth of fake news makes users insecure when they consume information. While text-based news is perhaps the most widespread, video is gaining ground quickly, and has been transformed into informative content that can be manipulated, leading to misinformation among users. This article analyses 63 applications for mobile devices that enable the creation of deepfakes. An analysis of the apps is carried out by examining 16 indicators across three dimensions: description of the application, treatment of the image, and data protection. Each application has its peculiarities regarding the modification of the physiognomy of a person, especially their face. In some cases, the legality of the applications is questionable as they can impact people’s fundamental rights. The results demonstrate that, in many cases, the user is not informed of the technology used by the applications, nor the types of data that are collected. In conclusion the apps allow the generation of fake videos by manipulating the physiognomy of people, however, there is a lack of information surrounding the privacy policies of the data they collect. In addition, the use of these applications can damage the image and/or reputation of a person and even supplant their identity.
Keywords: Deepfake; disinformation; video manipulation; apps; mobile applications